Case Report: Off-label treatment of idiopathic hypereosinophilic syndrome with Omalizumab - Zhang, Zhiyu; Sun, Yingxin; Chen, Su-Ning (Frontiers in Pharmacology, 2023)
Idiopathic hypereosinophilic syndrome (IHES) is a rare disease characterized by causeless persistent hypereosinophilia and eosinophilia-associated end-organ damage. Current treatment modalities don’t meet the needs due to adverse events of steroids as first-line therapy and the limited efficacy of second-line treatments, underscoring the need for new therapeutic strategies. Here we presented two cases of IHES with different clinical manifestations that were both refractory to corticosteroids. Patient #1 experienced rashes, cough, pneumonia, and steroid-induced side effects. Patient #2 had severe gastrointestinal symptoms attributed to hypereosinophilia. They both had high levels of serum IgE, didn’t respond well to second-line treatments of interferon-α (IFN-α) and imatinib, and Mepolizumab was not accessible. We then innovatively switched to Omalizumab, an anti-IgE monoclonal antibody approved for allergic asthma and chronic idiopathic urticaria. Patient #1 was treated with Omalizumab 600 mg per month for 20 months; his absolute eosinophil count (AEC) decreased significantly and has stabilized at around 1.0×109/L for 17 months, with complete relief from erythra and cough. Patient #2 recovered promptly from severe diarrhea with a sharp drop in AEC after 3 months of treatment with omalizumab at 600 mg per month. Therefore, we concluded that Omalizumab may be a seminal therapeutic strategy for IHES patients who are refractory to corticosteroids, whether as long-term management of AEC or as an urgent intervention to address severe symptoms caused by eosinophilia.